2012
DOI: 10.1159/000338007
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Treatment of Whey Proteins in Cow’s Milk Results in Differential Inhibition of IgE-Mediated Mast Cell Activation Compared to T-Cell Activation

Abstract: Background: Cow’s milk (CM) hydrolysates are frequently used as milk substitutes for children with CM allergy. In hydrolysates, allergenic epitopes within CM proteins are diminished by enzymatic treatment. The aim of this study was to examine the allergenic and immunogenic properties of whey proteins during hydrolysis. Methods: During hydrolysis, samples were obtained at 0, 10, 15, 30, 45, 60, 75 and 90 min. Degradation was checked by HPLC and SDS-PAGE. Allergenic potential was analyzed by IgE crosslinking cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
(33 reference statements)
1
17
1
4
Order By: Relevance
“…While T cell activation is reduced more than 50% after 9 min of hydrolysis, it takes at least 20 min to reduce the basophil response to the same extent. This is in contrast to a previous study that showed a time-point with reduced allergenicity but retained immunogenicity [35]. Possible explanations for these contradictive results may be the different techniques and patient groups used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…While T cell activation is reduced more than 50% after 9 min of hydrolysis, it takes at least 20 min to reduce the basophil response to the same extent. This is in contrast to a previous study that showed a time-point with reduced allergenicity but retained immunogenicity [35]. Possible explanations for these contradictive results may be the different techniques and patient groups used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…As shown in previous experiments in which whey protein degradation was followed during the hydrolysis process, a concurrent degradation of BLG and ALA was shown [23]. This study also showed that the capacity to cause IgE-mediated mast cell activation is size dependent.…”
Section: Discussionsupporting
confidence: 85%
“…Degranulation of RBL-huFcεRI cells with pooled serum from CMA patients was performed as described previously [23]. Confluent growing RBL-huFcεRI cells (1×10 5 /well) in 96-wells flat bottom culture plate were sensitized o/n with 5 µg/ml commercially available human purified IgE (Chemicon/Millipore) and stimulated with 10 µg/ml rabbit anti-human IgE antibodies (Dako) in Tyrode’s buffer at pH 7.4 with 0.1% HSA (Sigma-Aldrich, St. Louis, USA) for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these peptide fragments significantly upregulated interferon (IFN)‐γ and interleukin (IL)‐10 production and downregulated IL‐4 secretion by murine splenocytes. A decreased allergenicity, confirmed by protein degradation, inhibition of mast cell degranulation, reduction of ear swelling, and reduction of T‐cell proliferation was also observed in whey protein concentrates after hydrolysis with a time‐dependent effect (Knipping and others ). Meulenbroek and others () stated that in some patients this time effect is not evident, indicating that the degree of hydrolysis is not decisive, but the presence and stability of IgE and T‐cell epitopes in the hydrolysates are recognized by individual patients.…”
Section: Effect Of Processing Food Matrix and Digestibility On Milkmentioning
confidence: 85%